Self-harmonics suppression rectenna for Wireless Power Harvesting - Rosemizi Abd Rahim (School of Computer and Communication Engineering, University Malaysia Perlis, 2014)
The purpose of self-harmonic suppression rectenna is to eliminate the using of a harmonic filter circuit in filtering the harmonic radiation and electromagnetic interference (EMI) in rectenna system. The motivation for this work has been inspired by the need for compact size, low cost, high efficient rectenna system and also very important is the design structure is simple in order to reduce the error during the fabrication process. In the response to these challenging demands, four designs of self-harmonic suppression microstrip patch antenna have been simulated, fabricated, measured and analysed.